Effectiveness of ultrasound guided interfascial hydrodissection with the use of saline anesthetic solution for myofascial pain syndrome of the upper trapezius: a single blind randomized controlled trial - Suarez-Ramos, Charidy; Gonzalez-Suarez, Consuelo; Gomez, Ivan Neil; Gonzalez, Maria Katherine; Co, Philippe Hubert; Llamas, Jose Alfonso (Frontiers in Rehabilitation Sciences, 2023)
Background: Myofascial pain syndrome (MPS) is described as pain that arise from myofascial trigger points (MTrPs) which is a hyperirritable spot within a taut band of skeletal muscle. A newer needling technique called the interfascial hydrodissection (IH), wherein anesthetic saline solution (ASS) is injected between the fascia of the muscles using ultrasound as guide. It is theorized that this technique blocks the nerve branches and improve gliding in between the muscle and fascia. Objective: To determine the short and long-term effects of interfascial hydrodissection using 2% Lidocaine and saline solution compared to dry needling with MPS of the upper trapezius on pain and quality of life using. Methods: This study is a single-blind randomized controlled trial where ultrasound guided IH with ASS was compared to dry needling (DN) of the MTrPs. Both groups were taught self-stretch exercises (SSE) to be done everyday after the procedure. Outcome measures were pain using the visual analogue scale (VAS) and quality of life assessment with EQ-5D-5L questionnaire. All participants were assessed by a blinded assessor before the intervention, immediately after, 10 and 30 minutes, one week, two weeks, four weeks, three months, and six months after the procedure. Data Analysis: Two-way mixed ANOVA and follow-up independent T-test were conducted for the outcome measures across several time points between the 2 groups. Results: A total of 46 participants with two dropouts were all included during the final analysis. Both groups demonstrated significant differences in VAS scores between baseline and the different time points, the IH+SSE group demonstrated the more significant effect size at as compared to the DN+SSE group. For EQ-5D-5L, no statistical differences were seen in all dimensions but there was a larger effect size for usual activities, pain/discomfort and anxiety/depression. Conclusion: Interfascial hydrodissection is a technique that can manage both short and long term symptoms of MPS. This could be utilized as an alternative management for those with chronic MPS of the upper trapezius.